Determination Of Quercetin In Michelia Champaca L. (Champa) Leaves And Stem Bark By Hptlc - HAFSA AHMAD,; ANURAG MISHRA,; RAJIV GUPTA,; SHUBHINI A. SARAF, (International Journal of Pharma and Bio Sciences, 2011)
Background: Michelia champaca L. (Magnoliaceae) popularly known as champa is a reservoir of numerous bio-markers, assuming great significance in view of its rich chemistry. Objective: In the present study a High Performance Thin Layer Chromatography method has been used for detection, and quantification of quercetin in Michelia champaca (leaves and stem-bark). Materials and Methods: Increasing serial dilutions of reference standard quercetin (200 to 1000 μg mL-1) were scanned at 366 nm to detect and quantify the concentrations of quercetin in the test samples. Results: The estimated values obtained from the same were 682.235, 498.518 μg mL-1for leaves and stem bark respectively, amounting to 68.223 and 49.851 mg/g in the drug samples respectively. Leaves were found to be the richest source of quercetin in Michelia champaca. Conclusion: The method provided a rapid and easy approach for detection and the quantitation of the bio-marker quercetin